Juridical Analysis of Polri's Role in Criminal Acts of Class I Narcotics Abuse for Yourself - Juhrin Pasaribu (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
The legal arrangement governing the implementation of the criminal act of class I drug abuse for oneself is Law Number 35 of 2009 concerning Narcotics junto Law Number 5 of 1997 concerning Psychotropics. The implementation role of the Police against the crime of class I drug abuse oneself is Non-Penal (Preemptive and Preventive) and Penal (Repressive). Factors constraining protection for the Examination of the Role of the National Police against class I narcotics abuse are Facilities and Facilities in Law Enforcement, Society, and Law Enforcement. Therefore, the community must actively eradicate narcotics abuse and not remain silent when they know about a narcotics-related crime.